2013
DOI: 10.4067/s0717-95022013000100022
|View full text |Cite
|
Sign up to set email alerts
|

Hypoplastic Anterior Tibial Artery Associated with Continuation of Fibular (Peroneal) Artery as Dorsalis Pedis Artery: A Case Report

Abstract: SUMMARY:Arterial variations of distal parts of lower limb are well documented. However, continuation of fibular artery as dorsalis pedis artery is a rare finding. Unusual course and distribution of the anterior tibial artery and fibular artery were observed during routine anatomical dissection of the right lower limb of an approximately 40-year-old male cadaver. The arteries of the crural region arose from the popliteal artery, as usual. However the anterior tibial artery was hypoplastic. The fibular artery wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…El-Saeed et al (2008) recorded a variation in the origin of the DPA where the peroneal artery gave rise to the DPA. This variation has been recorded by many authors (Vijayalakshmi et al;Kulkarni & Ramesh;Rajeshwari et al;Shetty et al, 2013;Kumari & Bharti;Cheung et al, 2017).…”
Section: Introductionsupporting
confidence: 66%
“…El-Saeed et al (2008) recorded a variation in the origin of the DPA where the peroneal artery gave rise to the DPA. This variation has been recorded by many authors (Vijayalakshmi et al;Kulkarni & Ramesh;Rajeshwari et al;Shetty et al, 2013;Kumari & Bharti;Cheung et al, 2017).…”
Section: Introductionsupporting
confidence: 66%
“…The condition of hypoplastic anterior tibial artery or variation, associated with continuation of fibular (peroneal) artery as dorsalis pedis artery, was also reported by Shetty et al [ 10 ].…”
Section: Discussionmentioning
confidence: 62%
“…Huber had observed six such cases (3%), Vijayalakshmi et al, had such four cases (8%) and Lappas et al, had three such cases (1.5%) in their dissection studies. Proportions of 7.1% (Adachi 1928), 24 5% (Keen 1961), 25 6% (Lippert 1985) 26 have also been reported in literature. Shetty et al, and Vaishnavi et al, also have reported one case each.…”
Section: Embryological Correlationmentioning
confidence: 59%